مخاطر الائتمان وأثرها على ربحية المصارف التجارية دراسة تطبيقية على المصارف التجارية الليبية - الأمين, حمزة عبد الله (Scientific Journal of University of Benghazi, 2021)
The aim of this research is to know the effect of credit risk on the profitability of Libyan commercial banks operating in Libya, and to achieve this Purpose, reliance was placed on the collection of financial data (budgets and published annual financial reports) for the research sample consisting of three commercial banks, namely the Bank (Al-Wahdah, Al-tejari Alwatani [National Commercial Bank], and Sahara). During the period between (2005-2010). Where the independent variable represented by credit risk was measured using (ratio of loan allocations to total loans), and the dependent variable represented in bank profitability was measured using (rate of return on assets, rate of return on equity, rate of return on deposits). For the purpose of analyzing the research data, the simple linear regression method and the Pearson correlation coefficient were used, and the analysis was performed using the statistical program (SPSS.23) to arrive at the results. The results of the research showed that there is a statistically and significant impact at (5%) for credit risk on the rate of return on assets and the rate of return on deposits of the Al-Wahda Bank, while there is no statistically significant effect at (5%) for credit risk on the rate of return on equity. There is also a direct correlation between credit risk, the rate of return on assets, and the rate of return on deposits in AlWahda bank, while there is an inverse correlation between credit risk and the rate of return on equity in AlWahda bank, and there is no statistically significant and significant impact when ( 5%) for credit risk on the rate of return on assets, the rate of return on equity and the rate of return on deposits of the Al-tejari Alwatani Bank [National Commercial Bank] and Sahara Commercial Banks, and there is an inverse correlation between credit risk, rate of return on assets, rate of return on equity and rate of return on deposits in Al-tejariAlwatani Bank [National Commercial Bank] and Sahara Commercial Banks. The two researchers recommended the necessity of adherence to the local and foreign laws and regulations represented in the decisions of the Basel Committee.